Case report of new-onset obstructive sleep apnea after carbon monoxide poisoning. Issue 2 (February 2021) - Yang, Xiaorong; Xie, Min; Tan, Lu; Li, Taomei; Tang, Xiangdong
Obstructive sleep apnea (OSA) is characterized by repetitive intermittent oxygen desaturation during sleep. Carbon monoxide poisoning (COP) is the second most common cause of death among non-medicinal poisonings, and oxygen therapy is the current standard of treatment for COP. We herein report a case of a 50-year-old woman diagnosed with severe OSA associated with COP. Both the OSA and COP gradually resolved by automatic continuous positive airway pressure (CPAP) therapy. New OSA symptoms appeared following the development of delayed encephalopathy after acute COP (DEACMP) 3 weeks later. Severe OSA was diagnosed 76 days after COP with an apnea–hypopnea index of 66 events/hour, and CPAP therapy was immediately administered. The patient's DEACMP symptoms and OSA both improved with CPAP therapy (her apnea–hypopnea index decreased to 32.4 and 16.5 events/hour at 161 and 204 days after COP, respectively). To our knowledge, this is the first case report of OSA caused by COP based on the occurrence and disappearance of OSA symptoms and laboratory findings associated with the emergence and improvement of DEACMP.